Pakloub zadního segmentu pánve řešený pomocí štěpu z fibuly – kazuistika - Frank, Martin; McCallum, J. R; Dědek, Tomáš (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2017)
Posttraumatic pelvic nonunions in combination with malposition are uncommon in the present-day era of modern pelvic surgery. The case describes a new surgical technique for treatment of the nonunion localized to iliosacral joint. A 42-year-old polytraumatized male presented with a pelvic fracture (type 61-C2.3) associated with a complex acetabular fracture. The patient was treated and the pelvis stabilized according to damage control principles (external fixation and pelvic C-clamp) and subsequently definitively treated according to principles of current pelvic surgery. The posterior pelvis was stabilized by bilateral S1 iliosacral screws, however the posterior pelvic ring injury on the left side was not well reduced. The result was a nonunion formation in the left sacroiliacal joit with screw loosening. Two attemps at bone grafting and repeat stabilization were done, but the nonunion did not heal. The end result was a nonunion through left sacroiliacal joint with destruction of the lateral part of sacral bone. The nonunion was treated with nonvascularised autologous fibular strut graft in combination with allogenic corticocancellous grafting. The fibular graft was placed into the bone void after the removal of the iliosacral screw. Radiographically the nonunion healed completely six months after the fibular grafting and the patient had improved clinical outcome. The described technique solves both instability and bone defect in posterior pelvic ring even in the case with low contact areas. The nonvascularised autologous fibular grafting is an effective technique for sacroiliac joint nonunion treatment even in case with large bone defect. Key words: pelvis; nonunion; fibular graft.
Keywords: Bone Transplantation; transplantace kostí; fibula; Adult; Humans; Pelvic Bones; nezhojené fraktury; dospělí; Acetabulum; mužské pohlaví; Fracture Fixation, Internal; pánevní kosti; vnitřní fixace fraktury; Fractures, Ununited; lidé; acetabulum; Fibula; Male